Sosialisasi Optimalisasi Penginderaan Jauh Guna Meningkatkan Stok Tangkapan Ikan di Daerah Padangdangan Kecamatan Pasongsongan - Soraya, Amelia; Al Khatami, Muhammad Joeang Tegar; Hujjatullah, Muhammad Al Arif; Irwanto, Indra; Alfisuma, Meria Zakiyah (Santri : Journal of Student Engagement, 2025)
The fisheries sector plays a vital role in Indonesia's economy, particularly for coastal communities. However, the abundant marine potential in Padangdangan Village, Pasongsongan Subdistrict, Sumenep Regency, has not been optimally utilized by local fishermen. Traditional fishing practices, carried out continuously in specific locations, have led to environmental degradation and the risk of overfishing, threatening the sustainability of marine ecosystems. To address these issues, a community service program was conducted by students of Universitas Trunojoyo Madura through the Merdeka Belajar Kampus Merdeka (MBKM) initiative. This program aimed to empower fishermen through the dissemination of remote sensing technology based on oceanographic parameters, such as sea surface temperature, chlorophyll-a, and salinity, to identify potential and sustainable fishing grounds. The methods employed included material presentations, interactive discussions, evaluation quizzes, and the provision of traditional fishing gear (bubu). Additionally, the Fish Apartment concept was introduced as a solution for sustainable conservation. The results showed an increased understanding among fishermen of remote sensing technology, the potential application of sustainable fisheries concepts, and significant community enthusiasm for supporting the initiative. In conclusion, this outreach successfully provided essential education to the people of Padangdangan Village, enhancing fishing efficiency, preserving fishery resources, and improving the welfare of local fishermen.